Bartter Syndrome Type 3: Phenotype-Genotype Correlation and Favorable Response to Ibuprofen - Yang, Xuejun; Zhang, Gaofu; Wang, Mo; Yang, Haiping; Li, Qiu (Frontiers in Pediatrics, 2018)
Objective: To investigate the phenotype-genotype correlation in different genetic kinds of Bartter syndrome type 3 in children. Methods: Clinical and genetic data of 2 patients with different mutations in Bartter syndrome type 3 was analyzed while the prognosis was compared after a 6-year follow-up or 2-year follow-up, respectively. Results: Bartter syndrome is a kind of autosomal recessive inherited renal disorder. The manifestation and prognosis of Bartter syndrome change with mutation types, and severe mutation were often accompanied with unfavorable prognosis. Comprehensive therapy with ibuprofen, antisterone, captopril, and potassium have remarkable effect, while ibuprofen may improve growth retardation partly. Conclusion: Bartter syndrome should be considered when children have unreasonable continuous electrolyte disturbance, metabolic alkalosis and growth retardation.As a genetic disease, its clinical features depend on the mutation type. It can be ameliorated by electrolyte supplementation, prostaglandin synthetase inhibitors, angiotensin-converting enzyme inhibitors and potassium-sparing diuretic. Considering the following electrolyte disturbances, infections, growth retardation, kidney failure and even death, Bartter syndrome need lifelong treatment, early diagnosis and treatment is the most important.